Communication Persuasive Influencer TikTok in Shaping Smartphone Image and Purchase Interest in Circle Generation Z - Soares, Emerenciana; Maella, Nur'annafi Farni Syam (Jurnal Multidisiplin Indonesia, 2025)
Generation Z is group consumer Which very influenced by The development of technology and social media, particularly TikTok, has led to this platform becoming not only a means of entertainment but also a promotional platform for influencers to market products, including smartphones. Which become need main Gene Z. Popularity influencer TikTok often considered capable of building audience trust through the number of followers, likes, views, And engagement, so that can influence interest buy. Study This aims to describe perception Generation Z to popularity influencer TikTok and its relationship with smartphone purchasing interest . The study used a descriptive qualitative approach. through content analysis. Data was obtained from several Smartphone promotional video uploaded by a popular TikTok influencer with over 500 followers thousand, along with comment audience Generation Z. Technique collection data Using documentation and observation, data analysis was conducted using the Miles & Huberman model through data reduction, data presentation, and conclusion drawing. The results of this study found that Generation Z's perception of the popularity of TikTok influencers in promote Smartphone no linear . Popularity tall ( followers on on 500 thousand And engagement rate tall) of course functioning as gate initial attention , but the key factors that shape public opinion and trigger Purchase Intention are the Credibility and Authenticity of influencer content.